2019
DOI: 10.1177/1758835919846806
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of osteoclast-like cell formation by leptin-induced soluble intercellular adhesion molecule secreted from cancer cells

Abstract: Background: Leptin is considered a tumorigenic adipokine, suggested to promote tumorigenesis and progression in many cancers. On the other hand, intercellular adhesion molecule-1 (ICAM-1) shows altered expression in a variety of benign and malignant diseases. Histologically, ICAM-1 expression is reported as proportional to cancer stage and considered as a potential diagnosis biomarker. The altered expressions of ICAM-1 and its soluble form in malignant diseases have gained interests in recent years. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Injection of ICAM-neutralizing antibody reduced the osteolytic process in tumour-bearing mice. These findings led the authors to speculate that sICAM could be a potential therapeutic target or diagnostic tool for bone metastases from lung and breast cancer [81].…”
Section: Leptin and Bone Metastasismentioning
confidence: 99%
“…Injection of ICAM-neutralizing antibody reduced the osteolytic process in tumour-bearing mice. These findings led the authors to speculate that sICAM could be a potential therapeutic target or diagnostic tool for bone metastases from lung and breast cancer [81].…”
Section: Leptin and Bone Metastasismentioning
confidence: 99%
“…In this study, we screened for secreted proteins in the co-cultured cancer cells and confirmed leptin as a positive regulator of PAI-1. Other secreted-proteins, such as MPS-1, ICAM-1, and PLOD2, have also been validated as critical downstream effectors of leptin in cancers [ 16 , 55 , 56 ]. MPS-1 was demonstrated to promote the leptin-induced growth of colorectal cancer via activating the JNK/c-Jun pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPS-1 was demonstrated to promote the leptin-induced growth of colorectal cancer via activating the JNK/c-Jun pathway [ 55 ]. Another study revealed that leptin provoked the JAK1/2, STAT3, FAK, ERK, and GSK3αβ signaling cascade to stimulate the production of soluble ICAM-1 in cancer cells, which induced osteoclast formation and enhanced tumor-induced osteolysis in vivo [ 56 ]. On the other hand, leptin-induced non-secreted proteins, such as OBR, PKM2, ACAT2, and SREBP-1, are also important for breast cancer evolution [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, both FAK and c-Src signaling stimulated the leptin-invadopodia of MCF10A normal breast epithelial cells and the migratory abilities of both MCF-7 and MDA-MB 231 breast cancer cells [ 189 ]. In addition, leptin-dependent activation of JAK1/2/STAT3/FAK/ERK/GSK3αβ signaling cascade in breast tumor cells enhanced the production of intercellular adhesion molecule 1 (ICAM-1), toward the development of breast cancer bone metastasis [ 190 ].…”
Section: Fak and The Breast Tmementioning
confidence: 99%